Traumatic peripheral nerve injuries: epidemiological findings, neuropathic pain and quality of life in 158 patients - Ciaramitaro, Palma; Mondelli, Mauro; Logullo, Francesco; Grimaldi, Serena; Battiston, Bruno; Sard, Arman; Scarinzi, Cecilia; Migliaretti, Giuseppe; Faccani, Giuliano; Cocito, Dario (Journal of the peripheral nervous system, 2010)
The objectives of this study were (1) epidemiological analysis of traumatic peripheral nerve injuries; (2) assessment of neuropathic pain and quality of life in patients affected by traumatic neuropathies. All consecutive patients with a diagnosis of traumatic neuropathies from four Italian centres were enrolled. Electromyography confirmed clinical level and site diagnosis of peripheral nerve injury. All patients were evaluated by disability scales, pain screening tools, and quality of life tests. 158 consecutive patients for a total of 211 traumatic neuropathies were analysed. The brachial plexus was a frequent site of traumatic injury (36%) and the radial, ulnar, and peroneal were the most commonly involved nerves with 15% of iatrogenic injuries. Seventy‐two percent of the traumatic neuropathies were painful. Pain was present in 66% and neuropathic pain in 50% of all patients. Patients had worse quality of life scores than did the healthy Italian population. Moreover, there was a strong correlation between the quality of life and the severity of the pain, particularly neuropathic pain (Short Form‐36 [SF‐36] p < 0.005; Beck Depression Inventory [BDI] p < 0.0001). Traumatic neuropathies were more frequent in young males after road accidents, mainly in the upper limbs. Severe neuropathic pain and not only disability contributed to worsening the quality of life in patients with traumatic neuropathies.